Functional measures developed for clinical populations identified impairment among active workers with upper extremity disorders - Gardner, Bethany T. (J Occup Rehabil, 2016)
PURPOSE: Few studies have explored measures of function across a range of health outcomes in a general working population. Using four upper extremity (UE) case definitions from the scientific literature, we described the performance of functional measures of work, activities of daily living, and overall health. METHODS: A sample of 573 workers completed several functional measures: modified recall versions of the QuickDASH, Levine Functional Status Scale (FSS), DASH Work module (DASH-W), and standard SF-8 physical component score. We determined case status based on four UE case definitions: 1) UE symptoms, 2) UE musculoskeletal disorders (MSD), 3) carpal tunnel syndrome (CTS), and 4) work limitations due to UE symptoms. We calculated effect sizes for each case definition to show the magnitude of the differences that were detected between cases and non-cases for each case definition on each functional measure. Sensitivity and specificity analyses showed how well each measure identified functional impairments across the UE case definitions. RESULTS: All measures discriminated between cases and non-cases for each case definition with the largest effect sizes for CTS and work limitations, particularly for the modified FSS and DASH-W measures. Specificity was high and sensitivity was low for outcomes of UE symptoms and UE MSD in all measures. Sensitivity was high for CTS and work limitations. CONCLUSIONS: Functional measures developed specifically for use in clinical, treatment-seeking populations may identify mild levels of impairment in relatively healthy, active working populations, but measures performed better among workers with CTS or those reporting limitations at work.